Evaluation of spiro metric parameters in traffic police men in a Metropolitan City - Santosh Rohidas Bokre; Sangita Deshpande; Anil Raosaheb Waghmare; Anjali Shete (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Introduction: Air pollution is a major environment related health threat. Air quality crisis in Indian cities is mainly due to emission from vehicles which include various particles and gases from vehicular emission. Traffic policemen who work in the busy traffic signal areas for years together are constantly exposed to this pollutant making them susceptible to its adverse effects, like respiratory and cardiovascular diseases. Objectives: To compare different parameters of pulmonary function test (PFT) between non-smoker controls and non-smoker traffic policemen, and also between smoker controls and smoker traffic policemen. Methods: This study was carried out in Department of Physiology among the government servants not exposed to traffic pollution and traffic policemen exposed to vehicular pollution. PFT was conducted in both these groups and parameters like vital capacity (VC), FEV1-force expiratory volume at the end of 1 second, ratio of forced expiratory volume at first second to forced vital capacity (FEV1/FVC%), mid-expiratory flow rate (FEV25-75%) and peak expiratory flow rate (PEFR) were measured and compared between these two groups. Results: In the present study, traffic policemen (non smoker) showed a statistically significant reduction in VC, FEV1, FEV1/FVC%, FEV25-75, and PEFR compared to controls (non smoker) whereas traffic policemen (smoker) showed a statistically significant reduction in VC, FEV1, FEV1/FVC%, FEV25-75%, and PEFR compared to controls (smoker). Conclusion: Significant reduction in all the parameters in traffic policemen compared to control group proves that preventive measures like pollution masks, regular breathing exercises, etc., have to be implemented at the workplace to reduce health hazards of continuous exposure to traffic dust.